2023
DOI: 10.1128/spectrum.02328-22
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rhizosphere Bacterial Communities to Near-Natural Forest Management and Tree Species within Chinese Fir Plantations

Abstract: Near-natural forest management is an important way to change the soil fertility decline and productivity reduction of pure Chinese fir plantations. At present, many detailed studies have been carried out on the impact of near-natural forest management on Chinese fir plantations at home and abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 106 publications
2
6
0
Order By: Relevance
“…The results of this study showed that Actinobacteria, Proteobacteria, Acidobacteria, Bacteroidetes, Firmicutes, Verrucomicrobia, Planctomycetes and Chloroflexi were the dominant phyla in the microbiomes of P. lactiflora cultivars, among which the relative abundance of Actinobacteria, Proteobacteria and Acidobacteria was much higher than that of other phyla. This finding has also been confirmed in Cathaya argyrophylla and Chinese fir [48,49]. We also noted that the rhizosphere bacterial communities associated with P. lactiflora exhibited high diversity and abundance.…”
Section: Discussionsupporting
confidence: 83%
“…The results of this study showed that Actinobacteria, Proteobacteria, Acidobacteria, Bacteroidetes, Firmicutes, Verrucomicrobia, Planctomycetes and Chloroflexi were the dominant phyla in the microbiomes of P. lactiflora cultivars, among which the relative abundance of Actinobacteria, Proteobacteria and Acidobacteria was much higher than that of other phyla. This finding has also been confirmed in Cathaya argyrophylla and Chinese fir [48,49]. We also noted that the rhizosphere bacterial communities associated with P. lactiflora exhibited high diversity and abundance.…”
Section: Discussionsupporting
confidence: 83%
“…In addition to aspects related to the host plant, data reported in the scientific literature converge in identifying the soil type as another key parameter that greatly influences rhizosphere microbial communities. Rhizomicrobiota composition and diversity are significantly affected by soil organic matter and pH, with lower pH values associated with less diversified communities [33,92,93,99].…”
Section: Rhizosphere Microbial Communitiesmentioning
confidence: 99%
“…Despite the differences related to the plant genotype and environmental factors, similarities in rhizomicrobiota composition and the presence of shared taxa selected from the surrounding bulk soil can be observed for all plants. Acidobacteria, Actinobacteria, Bacteroidetes, Chloroflexi, Firmicutes, Proteobacteria, and Verrucomicrobia are the main bacterial phyla generally found in the rhizosphere, whereas Ascomycota and Basidiomycota are among the dominant fungal groups [92,94,[99][100][101][102]. Recent work on an intercontinental scale and based on comparisons between microbial communities of the rhizosphere and bulk soils revealed that some bacterial groups, including Bacteroidetes and Proteobacteria, were consistently enriched in the rhizosphere, whereas other phyla (such as Acidobacteria, Chloroflexi, and Nitrospirae) were significantly less abundant in rhizosphere soils than in root-free soils [103].…”
Section: Rhizosphere Microbial Communitiesmentioning
confidence: 99%
“…Metagenomic data indicated the ubiquity of Planctomycetes in diverse ecosystems (Wiegand et al, 2018), encompassing soil (Stackebrandt et al, 1993; Wang et al, 2002; Buckley et al, 2006; Ivanova et al, 2016;), plant rhizosphere (Lei et al, 2023; Ravinath et al, 2022), seawater (Schlesner, 1994; Wiegand et al, 2020), freshwater (Schlesner, 1994; Wang et al, 2002; Dedysh et al, 2020), chlorinated water (Aghnatios and Drancourt, 2015), the human gastrointestinal tract (Cayrou et al, 2013), and very frequently in association with several algae (Bengtsson and Øvreås, 2010; Lage and Bondoso, 2011, 2012; Wiegand et al, 2020). However, the cultivation of Planctomycetes in pure axenic cultures has proven to be challenging, primarily attributed to their recalcitrance to grow on synthetic media and their inherently slow growth kinetics (Kaboré et al, 2020).…”
Section: Introductionmentioning
confidence: 99%